2019
DOI: 10.1111/ssqu.12590
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Food–Energy–Water Nexus Awareness Among the American Public*

Abstract: Objective Recently, much research in the physical sciences has been dedicated to identifying a nexus or connection between water, energy, and food. This research agenda, however, has not been sufficiently examined in the social sciences. This article examines the extent to which individuals demonstrate awareness of the three nexus elements: water–energy, energy–food, and food–water. Methods We use three awareness indexes as dependent variables and varying sociodemographic characteristics and aspects of environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Only 8% of the papers employed participatory social science methods, including expert interviews [48], household surveys [49,50] and focus group discussions [51]. This is in line with Hannibal and Portney's [52] findings that the nexus research, or the connection between water, energy and food, has not been sufficiently addressed in the social sciences. Field experiments were only employed by 4% of the studies, namely, Mortensen et al [53] on nutrient loops in arid-land rivers, Obade and Lal [54] on soil quality assessment, and Tran et al [55] on the suitability of a sulfur-based seed solution in the development of WEF nexus technology using sulfur chemicals that contain an air pollutant.…”
Section: Bibliometric Analysis Of Wef Nexus Publications Related To I...mentioning
confidence: 73%
“…Only 8% of the papers employed participatory social science methods, including expert interviews [48], household surveys [49,50] and focus group discussions [51]. This is in line with Hannibal and Portney's [52] findings that the nexus research, or the connection between water, energy and food, has not been sufficiently addressed in the social sciences. Field experiments were only employed by 4% of the studies, namely, Mortensen et al [53] on nutrient loops in arid-land rivers, Obade and Lal [54] on soil quality assessment, and Tran et al [55] on the suitability of a sulfur-based seed solution in the development of WEF nexus technology using sulfur chemicals that contain an air pollutant.…”
Section: Bibliometric Analysis Of Wef Nexus Publications Related To I...mentioning
confidence: 73%
“…Acceptance of water conservation strategies, such as using recycled water, might only gain greater public acceptance if there are higher levels of knowledge pertaining to current water use in agriculture. A recent national survey of U.S. adults found that a majority (53%) were knowledgeable of the connectivity between water and food production [ 88 ], recognizing the trade-offs and water concerns in agricultural food production. While the U.S. public has some water knowledge pertaining to agricultural use and concern about abundance, there is potentially a lack of knowledge pertaining to water resources themselves.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, awareness of any one nexus was linked to awareness of another nexus, for which they suggest the existence of a latent “nexus cognition construct.” This construct appears to be related to support of policies related to nexus elements (e.g., reducing the reliance on energy use for water). Building on that study, Hannibal and Portney () examined predictors of public awareness of the FEW nexus and found that concern about food waste was correlated with awareness of the food‐water nexus and awareness of water waste was correlated with water‐energy nexus. They concluded that concerns about waste seemed to play a large part in influencing some people to make a connection among food, energy, and water.…”
Section: Nexus Researchmentioning
confidence: 99%
“…Past research on the FEW nexus has mainly occurred within the natural sciences and engineering while the social sciences and accompanying human dimensions research has largely been absent (Hannibal & Portney, ). The importance of considering the human dimensions of the FEW nexus is twofold.…”
Section: Towards a Psychology Of The Food‐energy‐water Nexus: Costs Amentioning
confidence: 99%